Pemberlakuan Restorative Justuce pada Tindak Pidana Korupsi Dana Desa dengan Kerugian Kecil - Wahyu Taruna Wibowo (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The return of state financial losses does not eliminate the criminal penalty for perpetrators of corruption. However, differences in the application of Restorative Justice in corruption cases have created legal uncertainty, especially in resolving corruption cases that involve relatively small state financial losses. This study aims to examine and analyze the implementation of Restorative Justice for perpetrators of corruption in the management of village funds, which are often caused by administrative errors, lack of understanding, or weak supervision rather than intentional acts of enrichment. This type of research is Doctrinal, using the statute approach, namely legal research that focuses on the application and interpretation of normative legal provisions (laws and regulations) as well as a theoretical concept approach to understand justice in a restorative framework. The resolution of village fund corruption cases with small losses should ideally prioritize recovery of losses and community restoration, but cannot eliminate the criminal aspect entirely, so clear legal guidelines are needed to ensure fairness and legal certainty.